THERAPEUTIC SCHOOLS’ ROLE IN THE FORMATION OF STUDENTS’ CLINICAL THINKING ON RESULTS OF UKRAINIAN STUDENTS THERAPY OLYMPIAD (INTERNAL MEDICINE) - Vakalyuk, I.P.; Seredyuk, N.M.; Seredyuk, V.N.; Denina, R.V.; Mergel, T.V. (World of Medicine and Biology, 2015)
The article describes role of Ukrainian therapeutic schools in the formation of students’ clinical thinking on results of All-Ukrainian therapy Olympiad. Results of the Olympiad demonstrated that, despite the original schools, approaches to teaching therapy remains the only according to current standards for diagnosis and treatment of internal diseases. Therapy Olympiad (Internal Medicine) promotes creative students’ clinical thinking on the basis of the achievements as a country, and regional therapeutic schools.
Keywords: therapeutic school; Olympiad; therapy